What textual copying does not count as plagiarism? Elaborate examples and problem-solving - Atif Abdulhamid Katib; Bakr Bakr Kalo; Nadir Hamza Motair (Journal of Ideas in Health, 2022)
Scientists are motivated to publish original and high-quality articles. The only right way to accomplish that is through a long and daunting academic career. Sometimes illegal shortcuts and tortuous methods are attempted by some people. Bolstered with elaborate examples and problem-solving, this treatise explains the legal ways of textual copying and proper referencing techniques. Moreover, it teaches how to steer away from copyright violations. In addition, it warns off all forms of literary theft and the catastrophic consequences of research misconduct.